Plan estratégico para la contribución al mejoramiento de la competitividad en la avícola FÉNIX periodo 2023-2028 - Almeida Meza, Tyrone Agustín (2024)
This research project aimed to develop a strategic plan for Avícola Fénix dedicated to the breeding and marketing of broiler chickens in Tosagua Canton, Ángel Pedro Giler Parish, considered a developing company that aspires to be a leader in its locality and to Nacional level. What the company seeks is to implement strategies to contribute to the improvement of its productivity and satisfy the needs of its clients, for which a list of activities was proposed to meet the proposed objectives. First, a study of the internal part and external of the Avicola by applying an interview to the manager for the development of the situational study, likewise, a survey of the company's employees for the collection of information, then the PESTEL was developed as a micro analysis of the Avicola, the competitive profile matrix to know your positioning in the market and the SWOT matrix. Subsequently, the strategic and operational objectives and tasks to achieve these objectives were established through the SWOT matrix and the objectives matrix. As a third phase, an action plan was proposed for the period 2023 – 2028, describing the elements of strategic planning and the preparation of the Balanced Scorecard, recording the results obtained and successfully reflected in the conclusions.